ANALISIS EFEKTIVITAS DAN KONTRIBUSI PENERIMAAN PAJAK REKLAME, PAJAK BUMI DAN BANGUNAN TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN SIAU TAGULANDANG BIARO - Hebimisa, Marce Takasili; Sondakh, Jullie J.; Wangkar, Anneke (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
The Original Revenue is the receipts from the levy of local taxes, levies, wealth management,wealth management area separated, and other income. Income areas in the implementation of regional autonomy is expected to contribute in financing the public interest and the interests of individual communities. Advertisement tax, tax on land and buildings included in local taxes. The purpose of this study is to determine the level of effectiveness and the contribution of advertisement tax, land and building tax to the local revenue District of Siau Tagulandang Biaro. The method of analysis used is quantitative descriptive method, to analyze data the realization of advertisement tax, tax on land and buildings from the years 2014-2016.The results of the research the overall level of effectiveness of the advertisement tax revenue, land and building tax in the year 2014-2016 this is very effective. The contribution of advertisement tax, land and building tax in the year of 2014-2016 rated not optimal and the criteria included in the contribution is very less. Finance agency Kabupaten Siau Tagulandang Biaro preferably improve the function of the control in the collection of advertisement tax, tax on land and buildings to increase the tax contribution to Local Revenue Kabupaten Siau Tagulandang Biaro.Keywords : local Revenue, local taxes, effectiveness, contribution